Pressure‐controlled intermittent coronary sinus occlusion improves the vasodilatory microvascular capacity and reduces myocardial injury in patients with STEMI. Issue 2 (29th May 2021) - Scarsini, Roberto; Terentes‐Printzios, Dimitrios; Shanmuganathan, Mayooran; Kotronias, Rafail A.; Borlotti, Alessandra; Marin, Federico; Langrish, Jeremy; Lucking, Andrew; Ribichini, Flavio; ,; Kharbanda, Rajesh; Ferreira, Vanessa M.; et al.
Abstract: Background: Preliminary data suggest that pressure‐controlled intermittent coronary sinus occlusion (PICSO) might reduce the infarct size (IS) in patients with anterior ST‐elevation myocardial infarction (STEMI). However, the applicability of this therapy to patients with inferior STEMI and its exact mechanism of action is uncertain. Methods and results: Thirty‐six patients (27 anterior and 9 inferior) with STEMI underwent PICSO‐assisted‐primary percutaneous intervention (PPCI) and were compared with matched controls who underwent standard PCI (n = 72). Median age was 63 (55–70) years and 82% were male. Coronary microvascular status was assessed using thermodilution‐derived index of microcirculatory resistance (IMR) and the vasodilatory capacity was assessed using the resistive reserve ratio (RRR). IS and microvascular obstruction (MVO) were assessed using cardiovascular magnetic resonance imaging (CMR) within 48 h and 6 months of follow‐up. At completion of PPCI, IMR improved significantly in PICSO‐treated patients compared with controls in patients with either anterior (63.7 [49.8–74.6] vs. 35.9 [27.9–47.6], p  < 0.001) or inferior STEMI (60.0 [47.6–67.1] vs. 22.7 [18.4–35.0], p  < 0.001). RRR significantly improved after PICSO treatment for anterior (1.21 [1.01–1.42] vs. 1.73 [1.51–2.16], p  = 0.002) or inferior STEMI (1.39 [1.05–1.90] vs. 2.87 [2.17–3.78], p  = 0.001), whereas it did not change in controls compared with baseline. Patients treated with PICSO presented significantly less frequently with MVO (66.6% vs. 86.1%, p  = 0.024) and smaller 6‐month IS compared with controls (26% [17%–30%] vs. 30% [21%–37%], p  = 0.045). Conclusion: PICSO therapy may improve microvascular function and vasodilatory capacity, which contributes to reducing IS in patients with STEMI undergoing PPCI.